2019
DOI: 10.1111/1440-1681.13197
|View full text |Cite
|
Sign up to set email alerts
|

Swimming training reduces glucose‐amplifying pathway and cholinergic responses in islets from lean‐ and MSG‐obese rats

Abstract: Here, we investigate the effects of exercise training on glucose‐ and cholinergic‐induced insulin secretion in pancreatic islets from obese and lean rats. Male Wistar rats were treated with monosodium glutamate (MSG) for the first 5 days of life, while control (CON) rats received saline. At 21 days, the rats were divided into exercised (EXE) and sedentary (SED) groups. The EXE rats swam for 30 minutes, three times/week, for 10 weeks. After this, MSG‐SED rats showed hyperglycaemia, hypertriglyceridaemia and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Also, CTL animals increased nuclear activity, which may indicate the effect of exercise on protein synthesis. The MSG-induced obesity model promoted an increase in the Lee index, as well as the deposition of retroperitoneal and perigonadal body fats, that corroborates with studies which, that have already demonstrated a significant increase in these parameters and, therefore, the efficiency of the model for the induction of obesity in rats (14,15). The effectiveness of this experimental model is justified by the injuries that occur in several central structures in the paraventricular region, with the arcuate and ventromedial nuclei of the hypothalamus being the most affected sites, with 80% to 90% of the neurons responsible for controlling energy expenditure, food consumption and glycemic homeostasis (16).…”
Section: Discussionsupporting
confidence: 89%
“…Also, CTL animals increased nuclear activity, which may indicate the effect of exercise on protein synthesis. The MSG-induced obesity model promoted an increase in the Lee index, as well as the deposition of retroperitoneal and perigonadal body fats, that corroborates with studies which, that have already demonstrated a significant increase in these parameters and, therefore, the efficiency of the model for the induction of obesity in rats (14,15). The effectiveness of this experimental model is justified by the injuries that occur in several central structures in the paraventricular region, with the arcuate and ventromedial nuclei of the hypothalamus being the most affected sites, with 80% to 90% of the neurons responsible for controlling energy expenditure, food consumption and glycemic homeostasis (16).…”
Section: Discussionsupporting
confidence: 89%
“…Then, laparotomy was performed to collect the organs. Retroperitoneal and peritoneal fat were collected and weighed and standardized by body weight (Borck et al 2020).…”
Section: Euthanasia and Tissue Collectionmentioning
confidence: 99%
“…The animals were then desensitized in a carbon dioxide chamber and then euthanized by decapitation [7]. Retroperitoneal, Perigonadal, and brown fats were removed, weighed, normalized to g.100 g − 1 of body weight, and used to calculate body adiposity [2]. Blood was collected in heparinized tubes and centrifuged at 4 °C, at 12,000 RCF (g) for 10 min to measure the plasma biochemical profile.…”
Section: Euthanasia and Materials Collectionmentioning
confidence: 99%
“…The model of obesity induced by perinatal injections of monosodium glutamate is widely studied and known in the literature [1][2][3]. The main alteration determined in this model is the damage and cell death of neurons in the hypothalamic nuclei, mainly in the arcuate nucleus (ARC), where this neuronal loss impairs the signalling mediated by insulin and affects the energy balance of the organism [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation